An in vivo study of utricular hair cell degeneration and regeneration following animoglycoside induced damage of the mammalian inner ear - Walshe, Peter (Trinity College (Dublin, Ireland). School of Medicine. Discipline of Clinical Medicine, 2007)
The anatomy of the mammalian ear is similar between the different subspecies. This applies to the structure of the utricle in humans and in guinea pigs. Hence the choice of the guinea pig utricle allows any findings pertaining to the physiology, development and anatomy to be applied to the human inner ear with a high degree of confidence. It has been known for some time now that the mammalian inner ear has a certain limited capacity to regenerate after damage. It is not yet known however where the regenerative attempt arises at a cellular level. The middle layer of the utricle is the macula -a sensory organ of balance. It contains hair cells - the impulse generators and supporting cells - their associated metabolic support cells. In this study the maculae of thirty five guinea pigs were damaged by transtympanic membrane injection with gentamicin. The opposite ears served as controls. The maculae were harvested at 1 (ten animals), 2 (ten animals) and 4 weeks (ten animals) post gentamicin damage and analysed at light microscopy and transmission electron microscopy for changes in hair cell and supporting cell numbers. A further 5 animals were treated with gentamicin and also intraperitoneal taurine as a potential cytoprotectant. These animals were harvested at 2 weeks and the maculae examined at light microscopy and transmission electron microscopy.
Keywords: Biomedical Science, M.D.; M.D. Trinity College Dublin